Diffuse, adult-onset nesidioblastosis/non-insulinoma pancreatogenous hypoglycemia syndrome (NIPHS): review of the literature of a rare cause of hyperinsulinemic hypoglycemia - Dieterle, Martin P.; Husari, Ayman; Prozmann, Sophie Nicole; Wiethoff, Hendrik; Stenzinger, Albrecht; Röhrich, Manuel; Pfeiffer, Uwe; Kießling, Wolfgang Rüdiger; Engel, Helena; Sourij, Harald; Steinberg, Thorsten; Tomakidi, Pascal; et al. (Biomedicines, 2023)
Differential diagnosis of hypoglycemia in the non-diabetic adult patient is complex and comprises various diseases, including endogenous hyperinsulinism caused by functional β-cell disorders. The latter is also designated as nesidioblastosis or non-insulinoma pancreatogenous hypoglycemia syndrome (NIPHS). Clinically, this rare disease presents with unspecific adrenergic and neuroglycopenic symptoms and is, therefore, often overlooked. A combination of careful clinical assessment, oral glucose tolerance testing, 72 h fasting, sectional and functional imaging, and invasive insulin measurements can lead to the correct diagnosis. Due to a lack of a pathophysiological understanding of the condition, conservative treatment options are limited and mostly ineffective. Therefore, nearly all patients currently undergo surgical resection of parts or the entire pancreas. Consequently, apart from faster diagnosis, more elaborate and less invasive treatment options are needed to relieve the patients from the dangerous and devastating symptoms. Based on a case of a 23-year-old man presenting with this disease in our department, we performed an extensive review of the medical literature dealing with this condition and herein presented a comprehensive discussion of this interesting disease, including all aspects from epidemiology to therapy.
Gesehen am 21.09.2023